2007
DOI: 10.1007/s10310-006-0258-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red wood ant (Formica rufagroup) mounds on root biomass, density, and nutrient concentrations in boreal managed forests

Abstract: Red wood ants (Formica rufa group, RWAs) are common insects in boreal forests in Fennoscandia, and they build large, long-lived mounds as their nests. RWA mounds are enriched with carbon and nutrients, but little information is available about how they affect root distribution and the nutrient uptake of trees. In this study, we investigated the biomass, biomass density, nutrient concentrations, and amounts of fi ne (<2 mm) and coarse (>2 mm) roots in RWA mounds, and compared them with those of surrounding fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Nevertheless, because RWAs have a strong impact on many other invertebrates (Hawes et al 2002;Koivula and Niemelä 2003;Reznikova and Dorosheva 2004;Dorosheva and Reznikova 2006;Ohashi et al 2007), their distribution pattern can have serious consequences. The decrease of the number of RWAs towards the clear-cut area centre may result in a change of the density of other invertebrates that suffer from predation by and/or competition with RWAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, because RWAs have a strong impact on many other invertebrates (Hawes et al 2002;Koivula and Niemelä 2003;Reznikova and Dorosheva 2004;Dorosheva and Reznikova 2006;Ohashi et al 2007), their distribution pattern can have serious consequences. The decrease of the number of RWAs towards the clear-cut area centre may result in a change of the density of other invertebrates that suffer from predation by and/or competition with RWAs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that RWAs have great influence on the distribution and abundance of other ant species, and many other epigeic and arboreal invertebrates (e.g. spiders, carabids; Hawes et al 2002;Koivula and Niemelä 2003;Reznikova and Dorosheva 2004;Ohashi et al 2007; but see also Lenoir et al 2003). It was also observed that these ants may affect the behaviour of carabids, for example forcing them to change their foraging and moving strategies (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…However, we have to note here that stands from high-elevation sites (>1500 m a.s.l.) in the data (2006), Borken et al (2007), Brunner et al (2002), Clemensson-Lindell and , Eichhorn (1987), Eldhuset et al (2006), Finér (1989), Gaul et al (2008a), Gaul et al (2008b), Genenger et al (2003), Godbold et al (2003), Helmisaari and Hallbäcken (1999), Helmisaari et al (2007), Jentschke et al (2001), Majdi (2001), Meyer et al (1988), Murach and Wiedemann (1988), Murach (1984), Murach (1991), Nygaard and de Wit (2004), Ohashi et al (2007), Ostonen et al (2007), Persson and Ahlström (2002), Persson et al (1995), Pietikäinen et al (1999), Püttsepp et al (2006), Raspe et al (1989), Sandhage-Hofmann and Zech (1993), Schmid and Kazda (2002), Schneider and Zech (1991), Schneider (1990), Taskinen et al (2003), Ulrich and Pirouzpanah (1986), Van Praag et al (1988), Wiedey (1991).…”
Section: Elevational Dependence Of Fine Root Biomass In European Norwmentioning
confidence: 93%
“…While conducting the visual categorization, we were guided by the population morphology approach, established for wood ants by Gilev (2002); however, a threshold approach (Roff, 1996) was used for precise categorization (Figs 2 and 3). In our study several aspects of the colour patterns were considered, as both the shapes of melaninbased colour morphs, the percentage of melanized area and the Frouz et al, 2016), improve soil properties (Frouz & Jílková, 2008) and affect concentrations of macroelements in tree roots and thus regulate their growth (Ohashi et al, 2007). These insects regulate structure and biodiversity of forest plants and animal communities, contributing to seed dispersal (Gorb et al, 2000) and provide suitable habitats for numerous other invertebrates (Härkönen & Sorvari, 2014;Parmentier et al, 2014;Elo et al, 2016).…”
Section: Colour Pattern and Analysis Of Melanizationmentioning
confidence: 99%